The Influence of Transparency and Accountability of The “Amil Zakat Persatuan Islam” Institution on Muzakki Beliefs - Sidik, Fajar; Mubarrok, Dede Husni; Mujib, Haqibul (Syari'ah Economics, 2023)
This study aims to determine the effect of transparency and accountability on muzakki trust in the Islamic Union Amil Zakat Institution Ciamis Regency Service Office. The research uses an associative quantitative approach with a descriptive verification method, which describes the variables as they are and tests the relationship between variables through collecting, processing, analyzing and interpreting data from questionnaires. The results showed that the transparency variable has a positive and significant effect on muzakki trust, with a significance value of 0.000 <0.05, tcount 5.402> t table 1.665, and regression coefficient 0.438. Accountability also has a significant effect on muzakki trust with a significance value of 0.005 < 0.050, tcount 2.905 > t table 1.665, and regression coefficient 0.395. At the same time, transparency and accountability together have a positive and significant effect on muzakki trust with a Fcount value of 19.788> Ftable 3.06 and a significance value of 0.000 <0.05.